Development of Tangram Media in Mathematics Learning Flat Built Materials to Improve Self Efficacy in Class 2 of Kendalrejo Negeri Srengat Primary School - Mayang Aminin Hamid; Cindya Alfi; Mohamad Fatih (Edumaspul: Jurnal Pendidikan, 2024)
The research aims to develop tangram media in flat building material which plays a role in increasing the self-efficacy of Class 2 of Kendalrejo Srengat District Elementary School. Blitar. Rises uses research and development (R&D) methods. The development stages used are ADDIE, namely Analysis, Planning, Development, Implementation and Evaluation. The data used is primary data from the research location, the subjects are 11 grade 2 students. The data collection technique is through a questionnaire and interview process, but during the pre-practice stage, observations are made, material and media experts, as well as a questionnaire for N-gam exam students. According to the results obtained by material experts (93%) and media experts (100%) it was declared very valid, media feasibility (100%) was declared very feasible, and the gain in increasing self-efficacy using the N-gain formulation obtained a value of 0.7788 which was declared high. This shows that tangram learning media can increase students' self-efficacy.